Proces zarządzania ryzykiem w strategicznym controllingu projektów - Kozarkiewicz, Alina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
One of the main groups of concepts and instruments in strategic controlling of projects are concepts aimed at the assessment of project effectiveness and project performance measurement. Due to the fact that the assessment is based on the forecasts and assumptions, its results depend upon the proper identification and appraisal of risk connected with a project. There are some specific methods prepared to assess projects in the conditions of risk, such as for instance sensitivity analysis, scenario methods or simulation, however, such methods cannot be properly used without the identification of risk sources, scope, positive and negative influences. The properly conducted risk management process seems to be the crucial part of the assessment of any project. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 165-173